SMU in partnership with Tax Academy of Singapore launches new Centre for Excellence in Taxation - Singapore Management University (Institutional Knowledge at Singapore Management University, 2014)
In collaboration with the Tax Academy of Singapore, and with the support of the Inland Revenue Authority of Singapore, the Singapore Management University has launched the SMU-TA Centre for Excellence in Taxation (SMU-TA CET) today. The SMU-TA CET represents a major new initiative in research addressing international and regional tax issues and taxation policies. It is the first research centre of its kind in Singapore. The aim of the Centre is to produce highly robust research in international and regional tax issues for policy-development and engagement of the international tax community.